Appellative Constructions with Epistemic Modality Predicates - E. R. Ioanesyan (Научный диалог, 2023)
The object of the study is parenthetical constructions, represented in the language by three types — modal, reflexive and appellative. Modal introductory constructions denote the modal status of a proposition. In reflexive introductory constructions, epistemic units act as reflection marking. Appellative introductory constructions have an illocutionary function — the function of influencing the addressee. The purpose of this article is to analyze appellative constructions with epistemic predicates — one of the subclasses of propositional attitude predicates, verbs of knowledge, perception and opinion. The relevance of the study is due to the fact that epistemic predicates play an important role in the processes of communication and argumentation. The results of a comparative analysis of appellative constructions in several languages — Russian, Polish, Bulgarian, Ukrainian, German, English, Italian, Spanish and Portuguese are presented. Particular attention is paid to the comparison of matrix constructions with epistemic predicates, that is, constructions with a dependent clause, and appellative constructions with these predicates. The analysis of translations of foreign texts with matrix constructions into Russian made it possible to conclude that there is a tendency to replace the original matrix constructions with introductory ones, and vice versa, the analysis of translations of texts from Russian with introductory constructions indicates a tendency to replace them with matrix ones.